Comparison of the effects of eldecalcitol with either raloxifene or bisphosphonate on serum tartrate resistant acid phosphatase-5b, a bone resorption marker, in postmenopausal osteoporosis - Takada, Junichi (Clin Cases Miner Bone Metab, 2016)
OBJECTIVE: This study analyzes whether concomitant raloxifene (RLX) or bisphosphonates (BP) plus eldecalcitol (ELD) has excessive suppressive effects on a bone resorption marker during the first 6 months of treatment in postmenopausal women in real-world setting. METHODS: 285 postmenopausal osteoporotic patients who had been treated with RLX or BP plus ELD were evaluated the bone resorption marker, serum tartrate resistant acid phosphatase-5b (TRACP-5b), during the first 6 months of treatment. RESULTS: In drug-naïve group (not received osteoporosis medications before the administration, n=70), the concomitant RLX or BP with ELD significantly decreased levels of TRACP-5b without severe suppression. In vitamin D switch group [RLX or BP plus alfacalcidol (ALF) and then switched to RLX or BP plus ELD, n=215], the replacing ALF with ELD further and significantly decreased TRACP-5b and tertile analyses based on baseline values were significantly decreased far more in the highest, compared with the lowest tertile in the ELD+RLX and ELD+BP groups. CONCLUSION: ELD combined with RLX or BP administered for 6 months to postmenopausal women with osteoporosis who were drug-naïve or who had switched medications significantly reduced and maintained TRACP-5b values within the reference range.